STUDENTS POSITIVE RESPONSE THROUGH THINK PAIR SHARE STRATEGY ON ENGLISH SPEAKING SKILLS - Iin Baroroh Ma’arif; Ashlihah Ashlihah (Eltin Journal : Journal of English Language Teaching in Indonesia, 2017)
Harmonious communication has an important role in teaching and learning process, especially in encouraging the success of teaching and learning process in the classroom. This research was conducted to know the student's response to the implementation of Think Pair Share strategy in Speaking course. This strategy emphasizes how students are more active in communicating using English in the classroom. The purpose of this research is 1) how the implementation of Think Pair Share strategy in class; 2) how students respond to the Think Pair Share strategy in the classroom; The design of this study is descriptive-qualitative to answer these questions. In this study, researchers themselves are the main instrument. In collecting data, researchers used observation sheets, and field notes.